Fullerenes on a Nanodiamond Platform Demonstrate Antibacterial Activity with Low Cytotoxicity - Olga Bolshakova; Vasily Lebedev; Elena Mikhailova; Olga Zherebyateva; Liliya Aznabaeva; Vladimir Burdakov; Yuri Kulvelis; Natalia Yevlampieva; Andrey Mironov; Igor Miroshnichenko; Svetlana Sarantseva (MDPI AG, 2023)
Carbon nanoparticles with antimicrobial properties, such as fullerenes, can be distinguished among the promising means of combating pathogens characterized by resistance to commercial antibiotics. However, they have a number of limitations for their use in medicine. In particular, the insolubility of carbon nanoparticles in water leads to a low biocompatibility and especially strong aggregation when transferred to liquid media. To overcome the negative factors and enhance the action of fullerenes in an extended range of applications, for example, in antimicrobial photodynamic therapy, we created new water-soluble complexes containing, in addition to C60 fullerene, purified detonation nanodiamonds (AC960) and/or polyvinylpyrrolidone (PVP). The in vitro antibacterial activity and toxicity to human cells of the three-component complex C60+AC960+PVP were analyzed in comparison with binary C60+PVP and C60+AC960. All complexes showed a low toxicity to cultured human skin fibroblasts and ECV lines, as well as significant antimicrobial activity, which depend on the type of microorganisms exposed, the chemical composition of the complex, its dosage and exposure time. Complex C60+PVP+AC960 at a concentration of 175 µg/mL showed the most stable and pronounced inhibitory microbicidal/microbiostatic effect.